Progress in Performance of AlGaN‐Based Ultraviolet Light Emitting Diodes - Jing Lang; Fujun Xu; Jiaming Wang; Lisheng Zhang; Xuzhou Fang; Ziyao Zhang; Xueqi Guo; Chen Ji; Chengzhi Ji; Fuyun Tan; Yong Wu; Xuelin Yang; et al. (Advanced Electronic Materials)
Abstract AlGaN‐based ultraviolet light‐emitting diodes (UV‐LEDs) have the advantages of mercury (Hg) pollution free, small size, high efficiency, and so on, and are widely used in military, medical, and industrial fields, which are considered to be the most promising alternative to the traditional Hg lamps. Great efforts are made over the past few decades to improve the device performance, thereby meeting the commercial production and application requirements of UV‐LEDs, which is always accompanied by a series of interesting physical topics. In this review, the recent research progress in performance of AlGaN‐based UV‐LEDs is summarized from the perspectives of electrical injection, electro‐optical conversion, and light extraction, which are responsible for the operation of devices. The detailed discussions include the major challenges, the corresponding technological breakthroughs, and also the outlook of material growth, energy band modulation, as well as device fabrication involved in UV‐LEDs, which are expected to be helpful for the thorough comprehension of device physics and further development of AlGaN‐based UV‐LEDs.